Preserving Tradition: Addinging-dinging as a Foundation of Cultural Identity in the Modern Era - Dafirah, Dafirah; Pammuda, Pammuda (Proceeding of International Joint Conference on UNESA, 2025)
This article discusses the role of the addinging-dinging tradition as a foundation of cultural identity in the modern era. The addinging-dinging tradition is one that is still routinely practiced every year by the Tenro community in the Selayar Islands Regency. Through a qualitative approach, this research explores the cultural values embedded in addinging-dinging tradition, as well as how these values reinforce the community’s sense of identity. Additionally, the article highlights the active role of the younger generation in preserving this tradition, as well as the challenges posed by globalization and modernization. The research findings indicate that addinging-dinging tradition not only serves as a means of entertainment but also as a medium for conveying local wisdom and building community solidarity. By involving the younger generation, this tradition can continue to adapt and remain relevant amidst the changing times. The influence of globalization and technology can strengthen the addinging-dinging tradition to be recognized more widely, not just in the Selayar region but throughout Indonesia and even on the international stage. The addinging-dinging tradition, which was previously known only to its local community, can now transcend boundaries due to globalization and modern technology. It is hoped that these findings will provide insights into the preservation of cultural values in the context of an increasingly modern society.